Antecedent factors influencing teachers readiness in teaching design and technology education - Endot, Zaleha; Jamaluddin, Rahimah (Universiti Tun Hussein Onn Malaysia, 2023)
Teacher readiness is necessary in the teaching and learning process, especially when a new curriculum is introduced. This study was conducted to identify the factors that influence the readiness of teachers in teaching Design and Technology (RBT) in the new Primary School Standard Curriculum (KSSR). The factors studied included self-efficacy, intrinsic motivation, ICT skills, and support training, which were the independent variables, and teacher readiness was the dependent variable. This descriptive quantitative survey involved 368 RBT teachers teaching Year 4 KSSR students in Peninsular Malaysia. Cluster and simple random sampling were used to select the sample of this study. The research instrument consisted of a set of questionnaires that contained 114 items adapted from previous research. A pilot study was conducted with a Cronbach’s Alpha value of 0.95. Study data were analyzed using Statistical Package for the Social Sciences (SPSS) software. The results of the study show that the overall mean for teachers’ readiness in teaching RBT is high. The findings showed that the overall mean for the aspect of reasoning knowledge was 3.82 (SP = .57) and SBA skills were 3.92 (SP = .58). Findings give the impression that the respondents have high reasoning knowledge and PBS skills. It was also found that the mean value for the aspect of SBA skills is higher than the reasoning knowledge. The regression analysis results show that all four factors significantly contribute to teacher readiness at 40.4 %. In conclusion, the findings of this study give the impression that the factors influencing teacher readiness are important in the formulation of a new curriculum. This study provides guidance to policy makers and curriculum planners especially for Ministry of Education Malaysia (KPM) on the aspect of teacher readiness when introducing new subjects.